Development of thrombosis in patients with and without SARS-Cov-2 infection - literature review (Research, Society and Development, 2021)
Venous thrombosis is characterized by excessive accumulation of structures composed of fibrins and platelets inside veins, causing partial obstruction or occlusion, usually affecting the lower limbs. The main risk factors for blood ssis, endothelial injury and hypercoagulability states stand out, intensifying with advancing age. Correlate the development of thrombosis in healthy patients and with those affected with COVID-19. The search for scientific articles was carried out in the electronic databases: Scientific Electronic Library Online (SCIELO), Latin American Literature in Health Sciences (LILACS), National Library of Medicine and the National Institute of Health (PubMed). Regarding the occurrence of thrombotic events in COVID-19, thrombosis is believed to be triggered by the "cytokine storm" which is the presence of an exacerbated level of proinflammatory cytokines in the blood. Due to the fact that many conditions present, on clinical examination, a picture similar to those found in thrombosis patients, it is necessary to perform more specific tests, but it is indispensable the research of D-dummer, which is the result of simultaneous coagulation and fibrinolysis, therefore it is exacerbated in suspected venous thrombosis, on the other hand, low d-dummer rate dispenses such suspicion. It was possible to observe a scarcity of specific literature on the development and installation of thrombosis. Studies on thrombosis in COVID-19 show that this pathology will not always develop secondary to infection, but in patients who have risk factors for the development of thrombosis the possibilities of development increase.